HEIDEGGER’S HUMAN DIMENSION UNDERSTANDING OF TECHNOLOGY - Uliana R. Vynnyk (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The aim of the research is to identify M. Heidegger's human dimension approach to the issue of technology .It is achieved by means of applying methods of analysis and synthesis in relation to philosopher’s philosophical and technical ideas. Scientific novelty. Philosopher’s important human dimension trends concerning technology are outlined in the research and are manifested in the concern for individuals to keep their humanity and dignity and make for the freedom eliminating everything that may adversely affect their essence.(немного поменяла слова и их порядок) The term "individual measurability" involves a process of spiritual and intellectual development of a man and, in this context, through his development and humanity one should evaluate everything created by him; technical, social progress should be seen primarily from the point of view of a free man, humane, rationally and existentially independent from the artificially created world, who is able to play an advanced role in the process of his own development, social progress and technology. Techniques and technologies, in their turn, should progress, based primarily on human needs. Individuals, coexisting with technical means should take everything that is good for them and simultaneously use them for their spiritual and personal development. Conclusion. Having occupied a special position in relation to the tradition of European criticism, the philosopher considered technology, its essence and specificity, as well as features of technical activities in different historical periods to be a subject of a positive philosophical analysis. Heidegger broke with the tradition of European philosophy of technology, which focused its attention on the direct, "obvious" achievements of progress, having showed that the effects of intrusion of technology are diverse and difficult to be predicted in the long run. Technological dependence is hardly fatal to humans in the sense that it contains distinct preconceived thinking, behavior and consciousness.